School rituals: Notes on school Games and olympics as rituals - doi: 10.4025/reveducfis.v23i2.13621 - Ana Gabriela Alves Medeiros; Fernanda Gonçalves Rios; Thaíse Ramos Varnier; Etyelle Ribeiro; Otávio Tavares (Revista da Educação Física)
Sociological theory suggests that all societies create ways of celebrating their values and identity. According to authors such as DaCosta (2000) and MacAloon (1984), Olympic Games are guided by values of the western modernity and celebrate them through its ceremonies. In the school context, a high number of “games” and/or “Olympics” might be identified, which, directly or indirectly, are based in the Olympic model. Thus, we aimed to analyze the meanings of values involved in the realization of these school games, focusing in the opening ceremonies. Moreover, we intended to understand the reasons that guide teachers to organize such competitions. For doing so, two schools ceremonies were observed and interviews were made with teachers who organized the competitions. We found that the appropriation of the values ​ ritualized in OG is singular, based on local realities, but coexist with the emulation of a universal model that is proposed.